2016
DOI: 10.1007/s10329-016-0575-6
|View full text |Cite
|
Sign up to set email alerts
|

Testing for links between face color and age, dominance status, parity, weight, and intestinal nematode infection in a sample of female Japanese macaques

Abstract: Studies of the role of secondary sexual ornaments in mate choice tend to focus on colorful traits in males, but females of many animal species express colorful ornamentation too. Among non-human primates, investigations into the role of female secondary sexual traits as indicators of life history characteristics, reproductive success, and health status have mostly focused on sexual swellings, whereas only few studies have been conducted on the role of facial color. Recent studies on rhesus macaques and mandril… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 80 publications
0
5
0
Order By: Relevance
“…The JM were studied on Koshima Islet, Miyazaki prefecture, Japan (31°27′N, 131°22′E), an area of approximately 30 ha covered with evergreen broadleaf forest (Duboscq, Romano, Sueur, & MacIntosh, 2016). Our study group (i.e., main group) was well habituated and has been well studied since 1948, through collection of demographic, ecological, behavioral, and life‐history data (Duboscq et al, 2016; Kawai, 1963; Rigaill et al, 2017; Watanabe, 1989, 2008; Yamagiwa, 2010). When the study started, the group consisted of 55 individuals, including 12 male and 24 female adults, 4 female and 3 male subadults, 5 male and 5 female juveniles, and 2 infants, 1 male and 1 female.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The JM were studied on Koshima Islet, Miyazaki prefecture, Japan (31°27′N, 131°22′E), an area of approximately 30 ha covered with evergreen broadleaf forest (Duboscq, Romano, Sueur, & MacIntosh, 2016). Our study group (i.e., main group) was well habituated and has been well studied since 1948, through collection of demographic, ecological, behavioral, and life‐history data (Duboscq et al, 2016; Kawai, 1963; Rigaill et al, 2017; Watanabe, 1989, 2008; Yamagiwa, 2010). When the study started, the group consisted of 55 individuals, including 12 male and 24 female adults, 4 female and 3 male subadults, 5 male and 5 female juveniles, and 2 infants, 1 male and 1 female.…”
Section: Methodsmentioning
confidence: 99%
“…When the study started, the group consisted of 55 individuals, including 12 male and 24 female adults, 4 female and 3 male subadults, 5 male and 5 female juveniles, and 2 infants, 1 male and 1 female. Sex, age, and kin‐relationships were already known (Duboscq et al, 2016; Kurita, Suzumura, Kanchi, & Hamada, 2012; Rigaill et al, 2017; Watanabe, 2008; Yamagiwa, 2010). Although the group lives on an island, this becomes occasionally connected to the mainland, allowing some exchange of individuals between groups.…”
Section: Methodsmentioning
confidence: 99%
“…Hindquarter coloration may also contain information about the inter-cycle probability of conception (Rigaill et al, 2019). Lastly, there is some evidence that skin coloration may reflect inter-individual variation (e.g., social rank, weight, but not parity, Rigaill et al, 2017Rigaill et al, , 2019. Pflüger and colleagues (2014) showed that males increased attention toward an experimentally intense red-coloured version of an unknown female face.…”
Section: Introductionmentioning
confidence: 99%
“…Hindquarter colouration may also contain information about the inter-cycle probability of conception (Rigaill et al, 2019). Lastly, there is some evidence that skin colouration may reflect inter-individual variation (e.g., social rank, weight, but not parity, Rigaill et al, 2017Rigaill et al, , 2019. Pflüger and colleagues (2014) showed that males increased attention toward an experimentally intense red-coloured version of an unknown female face.…”
Section: Introductionmentioning
confidence: 99%